Web-based visualization for 3D data in archaeology: The ADS 3D viewer. (October 2016) - Galeazzi, Fabrizio; Callieri, Marco; Dellepiane, Matteo; Charno, Michael; Richards, Julian; Scopigno, Roberto
Abstract: The solid geometry of archaeological deposits is fundamental to the interpretation of their chronological sequence. However, such stratigraphic sequences are generally viewed as static two-dimensional diagrammatic representations which are difficult to manipulate or to relate to real layers. The ADS 3D Viewer is a web-based resource for the management and analysis of archaeological data. The viewer was developed to take advantage of recent developments in web technology, namely the adoption of WebGL (Web Graphics Library) by current web browsers. The ADS 3D Viewer combines the potential of the 3D Heritage Online Presenter (3DHOP), a software package for the web-based visualization of 3D geometries, with the infrastructure of the Archaeology Data Service (ADS) repository, in the attempt to create a platform for the visualization and analysis of 3D data archived by the ADS. Two versions of the viewer have been developed to answer the needs of different users. The first version, the Object Level 3D Viewer, was implemented to extend the browsing capability of ADS project archives by enabling the visualization of single 3D models. The second version, the Stratigraphy 3D Viewer, is an extension which allows the exploration of a specific kind of aggregated data: the multiple layers of an archaeological stratigraphic sequence. This allows those unable to participate directly in the fieldwork to access, analyse and re-interpret the archaeological context remotely. This has the potential to transform the discipline, allowing inter-disciplinary, cross-border and 'at-distance' collaborative workflows, and enabling easier access to and analysis of archaeological data. Highlights: The ADS 3D Viewer provides a web-based system for the management and analysis of archaeological 3D data. The ADS Object Level 3D Viewer allows the dynamic visualization of single 3D models directly in the ADS project webpage. The ADS Stratigraphy 3D Viewer is a specialized tool for the visualization and analysis of archaeological stratigraphy. The ADS 3D Viewer allows those who are not in the field to access and analyse the archaeological context remotely. This work helps transform the discipline, allowing inter-disciplinary and 'at-distance' collaborative workflows.